Hatari! [videorecording (DVD)] - Wayne, John, 1907-1979; Krüger, Hardy, 1928-; Martinelli, Elsa, 1935-2017; Buttons, Red, 1919-2006; Blain, Gérard; Cabot, Bruce, 1904-1972; Girardon, Michèle, 1938-1975; Kurnitz, Harry (Paramount Pictures, 2005)
John Wayne heads a group of highly skilled professional game hunters in Africa who capture the ferocious big game with strong rope and cameras for zoos and circus attractions.